PROJECT APPLICATION & MONITORING SYSTEM (PROCAMS) FOR MIRI RESIDENT OFFICE - Chong, Siew Ting (Universiti Malaysia Sarawak (UNIMAS), 2019)
There are several project application and monitoring system developed to ease the officers to monitor the project application progress. Project application and monitoring system (ProCams) is developed for Miri Resident Office based on their requirements. In this report, a study of designing a project application and monitoring system is carried out and proposed. The proposed web system contains two modules. The main module is for the district office to fill in the application form. They only can view, edit own application and view application report. The admin module is for the resident office to monitor the project application progress and manages report. District officer has no authorization to access. This system is developed to digitalize the project application process for Miri Resident Office. This system also allows project application process tracking and monitoring. Besides that, this system also can produce project application reports based on the need of different authorities. Only the authorized user such as officer from the district office and the resident office has the right to access the information in ProCams.